Vers une comparabilité plus normative des statistiques internationales de l'éducation : de l'éducation de masse aux compétences - Roser Cussó; Sabrina D'Amico (Les éditions de la Maison des sciences de l'Homme, 2005)
The comparability of UNESCO's international statistics on education has been questioned since the end of the 1980s, when other international agencies started producing their own educational data. This evolution coincides with the newly strategic role given to education in the context of "globalization", i.e. education and training contribute to help nations improve their economic competitivity in the international market. According to OECD or the World Bank, more emphasis should be placed on the comparability of education outputs than on the measurement of the development of "mass education": indicators should be used not only to compare the characteristics of national education systems but also to compare underlying political decisions. The latter would be evaluated based on performance criteria established by external assessments (students' "life-skills", cost efficiency...). This new kind of comparability, which was justified by the quest for better quality of data, is, in a sense, less robust from a statistical point of view, but more ambitious in terms of objectives and consequences.